General Chemistry Class Perspective On The Utilization Of Young Coconut water To Treat Fever Symptom - Ridho, Dimas; Juwitaningsih, Tita; Samosir, Rafidah Almira; Pratiwi, Alfira Julian; Ardila, Mutia; Kurniawan, Ekin Dwi Arif; Sianipar, Mirna Wulan Sari; Alisya, Syalwa Nur; Br. Hutahuruk, Novitasari; Tafonao, Firman Satria (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to analyze the perspectives of students from the Department of Mathematics enrolled in a General Chemistry class regarding the use of young coconut water as a natural remedy to treat fever symptoms. The research is grounded in the widespread trust of Indonesian society in herbal medicine, particularly young coconut water, which has been traditionally used across generations to treat various health conditions, including fever. Young coconut water is known to contain vital nutrients such as electrolytes (potassium, sodium, magnesium), B-complex vitamins, and vitamin C, which help lower body temperature naturally, especially during dehydration caused by fever. A quantitative approach with a descriptive survey method was employed. The data were collected using a closed questionnaire based on a Likert scale, which was tested for validity and reliability, achieving a Cronbach's Alpha value of 0.977-indicating a high level of reliability. Results showed that students' average scores in knowledge (3.90), understanding (3.81), attitude (3.89), and application (3.87) were all in the high category. This indicates that students not only understand the benefits of young coconut water but also grasp scientific concepts related to electrolyte function in fluid balance and immune response. Despite the high scores, some misconceptions persist. For example, a few students believe young coconut water can entirely replace medical treatment or that higher consumption leads to faster healing without regard for appropriate dosage. This highlights the need for improved science-based health literacy. The study concludes that continuous health education through lectures, seminars, and healthy campus campaigns integrating both traditional and medical approaches is essential. These findings are significant in promoting the wise and measurable use of natural remedies like young coconut water while avoiding misuse. Furthermore, the results can serve as a basis for future research, such as clinical trials or laboratory comparisons with other rehydration fluids, and can help develop health promotion policies in academic settings to encourage smart and healthy decision-making among students.